Le programme communautaire de garderies au Guatemala: un ciblage efficace de l'aide alimentaire dans les régions urbaines - Ruel, Marie T. (International Food Policy Research Institute, 2003)
The programme has a substantial positive impact on the diet of children. It also complements the basic livelihood strategies of poor urban women working outside the home.